DETERMINASI CAPITAL SRTUCTURE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK JAKARTA PERIODE 2000 - 2004 - Indrawati, Titik; Suhendro, Suhendro (UI Scholars Hub, 2006)
This study attempts to analyze the determinants of capital structure in the Indonesian manufacturing industry from 2000 to 2004. Empirical hyphoteses, drawn from five independent variables are tested against a sample of 49 firms or a cross sectional data. The results show that only In total asset (size), net operating income (NOI), and return on asset (ROA) affect long-term debt to total asset (leverage). It finds a p'ositive relation between leverage and In total asset, a negative relation between leverage andprofitability (NOI and ROA). Delta sales (growth) and ownership structure have no effect on leverage. These findings are stable in 2000 through 2004